Relationship Between Consumption of Sweetened Beverages and the Incidence of Diabetes Mellitus at the Menteng Community Health Center in Palangka Raya City - Elisa Dewi; Eva Prilelli Baringbing; Anggreni Ade Putri (PROMOTOR, 2026)
Diabetes mellitus (DM) is one of the non-communicable diseases that is a leading cause of death worldwide, with prevalence continuing to rise year after year. One of the risk factors contributing to the increase in DM cases is the consumption of sugar-sweetened beverages (SSBs). Common types of sugar-sweetened beverages consumed by the public include carbonated drinks (soda), ready-to-drink sugary tea and coffee, fruit juices with added sugar, energy drinks, sports drinks, and flavored milk. These beverages contain high amounts of added sugar and are easily accessible to people of all ages. The purpose of this study is to determine the relationship between the consumption of sugar-sweetened beverages and the incidence of diabetes mellitus at the UPTD Puskesmas Menteng in Palangka Raya City. The research method used is correlational with a cross-sectional approach. The sampling technique is accidental sampling, with a total of 85 individuals who sought treatment at the UPTD Puskesmas Menteng in Palangka Raya City. The analysis conducted was univariate and bivariate analysis using the chi-square test. The results of the study showed that the chi-square test yielded a p-value of 0.000 < 0.05, indicating a significant association between the consumption of sweetened beverages and the incidence of diabetes mellitus at the UPTD Puskesmas Menteng in Palangka Raya City. Conclusion: There is a significant association between the consumption of sweetened beverages and the incidence of diabetes mellitus. Promotive and preventive efforts are needed to educate the community.